Method for preparing novel ultra-high performance concrete material by using special fibers
Through the combination of special fibers, cement, mineral blends and refined wood ash, the problem of insufficient strength and durability of traditional concrete is solved, and the preparation of high-performance concrete is achieved, meeting the needs of modern construction, and providing environmentally friendly and sustainable Solution.
Patent Information
- Application Number
- CN202411329915.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Traditional concrete has low strength and poor durability, making it difficult to meet the needs of modern construction. At the same time, traditional reinforced fibers are costly and environmentally limited, and lack sustainable alternatives.
Special fibers are used to form high-strength and high-tough concrete by cooking, crushing and soaking bamboo fibers and using them together with cement, mineral blends and refined wood ash after being cooked, crushed and soaked, forming high-strength and high-tough concrete, improving the compressive and folding resistance of concrete. performance, and reduce construction difficulty and environmental pollution by optimizing raw material mix ratio and water reducing agent use.
It has achieved high compressive strength, flexural strength and durability improvement of concrete, significantly improved the performance of concrete, met the high-demand engineering needs, and provided green and sustainable solutions to enhance the seepage resistance and compactness of concrete. Spend.
Smart Images

Figure CN119217537A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a method for preparing a new ultra-high performance concrete material by utilizing special fibers. Background Art
[0002] With the continuous development of the construction industry, the performance requirements for concrete materials are getting higher and higher. Traditional concrete has problems such as low strength and poor durability, which makes it difficult to meet the needs of modern construction projects. Therefore, the development of new ultra-high performance concrete materials has important practical significance.
[0003] Ultra-High Performance Concrete (UHPC) is a new type of cement-based composite material with ultra-high strength, high durability and excellent working performance. It is usually composed of cement, silica fume, quartz sand, high-efficiency water reducer, steel fiber and other materials. It has high-strength compressive strength, which is several times the strength of ordinary concrete. At the same time, it has excellent impermeability, frost resistance, chemical corrosion resistance and wear resistance, and can maintain good performance for a long time under harsh environmental conditions.
[0004] With the increasing demand for sustainable development and environmentally friendly building materials, finding alternatives to traditional building materials such as composite fibers has become a research hotspot. Bamboo fiber, as a renewable, biodegradable and high-strength natural resource, shows great potential in replacing traditional reinforcing fibers.
[0005] Therefore, the present invention aims to provide a method for preparing a new ultra-high performance concrete material using special fibers, and add bamboo fiber as a new material to ultra-high performance concrete to improve its mechanical properties, durability and environmental protection. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a method for preparing a new ultra-high performance concrete material using special fibers, which solves the problem that traditional reinforcing fibers are relatively high in cost and have certain limitations in environmental protection.
[0007] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a new ultra-high performance concrete material using special fibers, comprising the following method steps:
[0008] S1. Raw material preparation: prepare wood ash, special fiber, cement, mineral admixture, fine aggregate, coarse aggregate, water reducer and water;
[0009] S2, raw material pretreatment: grinding the wood ash for refinement;
[0010] S3, mixing and stirring: adding cement, mineral admixture, fine aggregate and coarse aggregate into a mixer, dry mixing for a certain period of time, adding treated wood ash and special fiber, continuing to stir evenly, and then adding water and water reducing agent and continuing to stir;
[0011] S4. Forming and curing: pour the mixed concrete into a mold for forming. After curing, the formed concrete is cured to obtain a finished product of ultra-high performance concrete new material.
[0012] Preferably, the raw materials are respectively as follows by weight: 50-85 parts of wood ash, 15-75 parts of special fiber, 420-480 parts of cement, 110-145 parts of mineral admixture, 120-150 parts of fine aggregate, 100-150 parts of coarse aggregate, 15-30 parts of water reducer, and 170-280 parts of water.
[0013] Preferably, the method for manufacturing the special fiber comprises the following steps:
[0014] Step 1: saw and split the original bamboo into pieces with a length of 10 to 40 mm, and then boil the original bamboo pieces in boiling water for 2 to 3 hours;
[0015] Step 2: Take out the boiled bamboo pieces, crush them into bamboo strips, and then immerse the bamboo strips in a sodium hydroxide solution;
[0016] Step 3, immersing the alkali-boiled bamboo fiber in a softener treatment solution for soaking treatment;
[0017] Step 4: Soak the bamboo fiber obtained in step 3 in anhydrous ethanol, then wash it with tap water and dry it naturally.
[0018] Preferably, in step 2, the bath temperature is 100-110° C., the immersion time is 3-4 hours, and the bath ratio is 1:(25-30).
[0019] Preferably, in step three, the bath temperature is 45-55° C., the treatment time is 2-3 h, and the bath ratio is 1:(25-30).
[0020] Preferably, in the step S4, the formed concrete is cured for 15 to 20 days at a temperature of 25° C. and a relative humidity of 90%.
[0021] Preferably, the fine aggregate is quartz sand, river sand or machine-made sand, and the fineness modulus is between 2.4 and 2.8.
[0022] Preferably, the mineral admixture includes one or more of silica fume, fly ash and slag powder.
[0023] Preferably, the cement is one of Portland cement, high belite cement and sulphoaluminate cement.
[0024] Preferably, the wood ash has a fineness of 700-800 mesh after grinding, and the length of the special fiber is controlled to be in the range of 2-2.5 cm, and the diameter is 0.1-0.5 mm.
[0025] The present invention provides a method for preparing a new ultra-high performance concrete material using special fibers. The method has the following beneficial effects:
[0026] 1. The present invention adopts a specific preparation process, cement, mineral admixtures and specially treated wood ash to synergistically provide high compressive strength and flexural strength for concrete, so that the concrete has good performance. The 30-day compressive strength can reach more than 200MPa, and the one-week flexural strength is also significantly higher than that of ordinary concrete, which can meet various high-demand engineering structure requirements.
[0027] 2. The present invention optimizes the mix ratio of raw materials and adds a water reducing agent, so that the concrete has a certain fluidity during the construction process, which is convenient for pouring and molding, especially for structures with complex shapes and areas with dense steel bars, and the construction difficulty is reduced. At the same time, the wood ash is ground and refined and then added to the concrete, which not only realizes the recycling of waste and reduces pollution to the environment, but also brings into play the potential activity of the wood ash. The fine particles of the wood ash can fill the pores in the concrete, improve the density of the concrete, and thus enhance the performance of the concrete.
[0028] 3. The present invention uses special fibers made from raw bamboo through multiple processes, with length and diameter controlled within a specific range, to form a three-dimensional network structure in concrete, which significantly improves the tensile strength and toughness of concrete. The application of this natural fiber provides a green and sustainable solution for the reinforcement of concrete. At the same time, due to the compact microstructure of concrete, its impermeability is far better than that of ordinary concrete. This enables concrete to effectively resist the penetration of water and other liquids under various harsh environments, such as humidity, chemical erosion, etc., and prolongs the service life of the concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 It is a preparation flow chart of the present invention. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Please refer to the attached Figure 1The present invention provides a method for preparing a new ultra-high performance concrete material using special fibers, comprising the following steps:
[0032] S1. Raw material preparation:
[0033] Wood ash, as a unique ingredient, has the potential to enhance the performance of concrete. Prepare 50 to 85 parts. Special fiber is a key factor in improving the strength and toughness of concrete. Prepare 15 to 75 parts. Cement is the main cementitious material. Select 420 to 480 parts. You can choose one of silicate cement, high belite cement, and sulphoaluminate cement. Different types of cement have their own characteristics and can provide a stable strength foundation for concrete. Mineral admixtures can improve the performance of concrete. They are composed of one or more of silica fume, fly ash, and slag powder. Prepare a total of 110 to 145 parts. Fine aggregate plays a role in filling and increasing the density of concrete. It is quartz sand, river sand or machine-made sand. The fineness modulus is strictly controlled between 2.4-2.8. Prepare 120 to 150 parts. Coarse aggregate provides skeleton support for concrete. Prepare 100 to 150 parts. Water reducer can reduce water consumption while maintaining the workability of concrete. Prepare 15 to 30 parts. The amount of water is 170 to 280 parts, and its quality also has an important impact on the performance of concrete.
[0034] S2. Raw material pretreatment:
[0035] The wood ash is finely ground to a fineness of 700 to 800 mesh. Through grinding, the wood ash particles become smaller and can be better mixed with other raw materials, giving full play to its potential activity, thereby improving the performance of concrete. This pretreatment step is crucial for the subsequent strength and durability of concrete.
[0036] S3, mixing and stirring:
[0037] Cement, mineral admixtures, fine aggregate and coarse aggregate are added to a high-efficiency mixer for dry mixing. During the dry mixing process, the components are initially mixed to lay the foundation for subsequent full combination. The dry mixing time is controlled within a certain range to ensure that the components are evenly distributed. After dry mixing, pre-treated wood ash and special fibers are added.
[0038] In this step, the special fiber manufacturing method used is as follows:
[0039] First, the original bamboo is sawed and split to make the length of the original bamboo slices within 10 to 40 mm. Such a length is convenient for subsequent processing and can play a good reinforcing role in concrete.
[0040] Next, put the raw bamboo chips into boiling water and boil them for 2 to 3 hours. Boiling water boiling can remove impurities and some lignin in the raw bamboo chips and prepare them for subsequent processing.
[0041] After the scouring, the original bamboo pieces are fished out and crushed into bamboo filaments. The formation of bamboo filaments increases the surface area of the fiber, which is conducive to the combination with other components. Then, the bamboo filaments are immersed in a sodium hydroxide solution for soaking. Under the conditions of a bath temperature of 100 to 110°C, an immersion time of 3 to 4 hours, and a bath ratio of 1: (25 to 30), the sodium hydroxide solution can further remove impurities and lignin in the bamboo filaments and improve the purity and strength of the fiber.
[0042] The alkali-boiled bamboo fiber is immersed in a softener treatment solution for soaking treatment. Under the conditions of a bath temperature of 45 to 55°C, a treatment time of 2 to 3 hours, and a bath ratio of 1: (25 to 30), the softener treatment solution can make the bamboo fiber softer, reduce the friction between the fibers, and improve the workability of the concrete.
[0043] Finally, the treated bamboo fiber is soaked in anhydrous ethanol, washed with tap water, and dried naturally to obtain the special fiber. The length of the special fiber is controlled to be 2 to 2.5 cm, the diameter is 0.1 to 0.5 mm, and it has good reinforcing effect and workability.
[0044] The fine particles of wood ash interact with other ingredients, and the special fibers form a three-dimensional network structure in the concrete, which significantly improves the tensile strength and toughness of the concrete. Continue stirring to mix these ingredients evenly, and then add water and water reducer. The addition of water reducer can reduce the water-binder ratio of concrete and improve the density and strength of concrete. During the mixing process, the mixing time and speed of each stage are carefully controlled to ensure the quality of the concrete is stable.
[0045] S4, molding and curing
[0046] Pour the mixed concrete into the mold for molding. During the pouring process, pay attention to controlling the pouring speed and method to avoid defects such as segregation and honeycomb. The molded concrete is cured under specific conditions. The curing temperature is 25°C, the relative humidity is 90%, and the curing time is 15 to 20 days. Such curing conditions can ensure that the concrete is fully hydrated and improve the strength and durability of the concrete. During the curing process, the concrete should be inspected and maintained regularly to ensure the stability of the curing conditions.
[0047] Through the above steps, the new ultra-high performance concrete material prepared using special fibers has excellent performance and can be widely used in engineering fields such as construction, bridges, and tunnels.
[0048] The present invention will be further described below in conjunction with specific embodiments.
[0049] Embodiment 1:
[0050] A method for preparing a new ultra-high performance concrete material using special fibers, comprising the following steps:
[0051] S1. Raw material preparation: prepare wood ash, special fiber, cement, mineral admixture, fine aggregate, coarse aggregate, water reducer and water;
[0052] S2, raw material pretreatment: grinding the wood ash for refinement;
[0053] S3, mixing and stirring: adding cement, mineral admixture, fine aggregate and coarse aggregate into a mixer, dry mixing for a certain period of time, adding treated wood ash and special fiber, continuing to stir evenly, and then adding water and water reducing agent and continuing to stir;
[0054] S4. Forming and curing: pour the mixed concrete into a mold for forming. The formed concrete is cured for 15 days at a temperature of 25° C. and a relative humidity of 90% to obtain a finished product of the ultra-high performance concrete new material.
[0055] The raw materials are calculated by weight as follows: 85 parts of wood ash, 75 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water. The fine aggregate is quartz sand, river sand or machine-made sand, and the fineness modulus is between 2.4 and 2.8. The mineral admixture includes one or more of silica ash, fly ash, and slag powder. The cement is one of silicate cement, high belite cement, and sulphoaluminate cement. The fineness of the wood ash after grinding is 700 mesh. The length range of the special fiber is controlled at 2 cm and the diameter is 0.5 mm.
[0056] Furthermore, in this embodiment, the method for manufacturing the special fiber includes the following steps:
[0057] Step 1: Saw and split the original bamboo into pieces with a length of 15 mm, and then boil the original bamboo pieces in boiling water for 2 hours;
[0058] Step 2: Take out the scoured bamboo pieces, crush them into bamboo strips, and then immerse the bamboo strips in a sodium hydroxide solution. In this step, the bath temperature is 105° C., the immersion time is 4 hours, and the bath ratio is 1:25.
[0059] Step 3: immerse the alkali-boiled bamboo fiber in a softener treatment solution for immersion treatment. In this step, the bath temperature is 55° C., the treatment time is 3 hours, and the bath ratio is 1:25;
[0060] Step 4: Soak the bamboo fiber obtained in step 3 in anhydrous ethanol, then wash it with tap water and dry it naturally.
[0061] Embodiment 2:
[0062] The preparation method adopted in this embodiment is consistent with that in Embodiment 1, except that the raw material components used are different. The raw materials in this embodiment are respectively calculated by weight as follows: 82 parts of wood ash, 65 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0063] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0064] Embodiment 3:
[0065] The preparation method adopted in this embodiment is consistent with that in Embodiment 1, except that the raw material components used are different. The raw materials in this embodiment are respectively calculated by weight as follows: 78 parts of wood ash, 60 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0066] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0067] Embodiment 4:
[0068] The preparation method adopted in this embodiment is consistent with that in Embodiment 1, except that the raw material components used are different. The raw materials in this embodiment are respectively, by weight: 75 parts of wood ash, 55 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0069] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0070] Embodiment 5:
[0071] The preparation method adopted in this embodiment is consistent with that in Example 1, except that the raw material components used are different. The raw materials in this embodiment are respectively, by weight: 70 parts of wood ash, 45 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0072] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0073] Embodiment 6:
[0074] The preparation method adopted in this embodiment is consistent with that in Embodiment 1, except that the raw material components used are different. The raw materials in this embodiment are respectively, by weight: 67 parts of wood ash, 35 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0075] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0076] Embodiment 7:
[0077] The preparation method adopted in this embodiment is consistent with that in Embodiment 1, except that the raw material components used are different. The raw materials in this embodiment are respectively calculated by weight as follows: 63 parts of wood ash, 30 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0078] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0079] Embodiment 8:
[0080] The preparation method adopted in this embodiment is consistent with that in Example 1, except that the raw material components used are different. The raw materials in this embodiment are respectively, by weight: 57 parts of wood ash, 25 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0081] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0082] Embodiment 9:
[0083] The preparation method adopted in this embodiment is consistent with that in Example 1, except that the raw material components used are different. The raw materials in this embodiment are respectively calculated by weight as follows: 53 parts of wood ash, 20 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0084] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0085] Embodiment 10:
[0086] The preparation method adopted in this embodiment is consistent with that in Embodiment 1, except that the raw material components used are different. The raw materials in this embodiment are respectively, by weight: 50 parts of wood ash, 15 parts of special fiber, 420 parts of cement, 110 parts of mineral admixture, 120 parts of fine aggregate, 120 parts of coarse aggregate, 15 parts of water reducer, and 180 parts of water, wherein the fine aggregate is quartz sand, the mineral admixture is fly ash, and the cement is Portland cement.
[0087] The test performance of the new ultra-high performance concrete material prepared in this embodiment is shown in Table 2.
[0088] Comparative Example:
[0089] This comparative example provides ultra-high performance concrete, and the preparation raw materials include the following component raw materials: 400 parts of silicate cement, 110 parts of quartz sand, 100 parts of gravel, 140 parts of fly ash, 20 parts of polycarboxylic acid water reducer, 40 parts of composite steel fiber, 25 parts of rice husk ash, and 230 parts of water.
[0090] The preparation method of the ultra-high performance concrete comprises the following steps:
[0091] S1. Mix gravel, fly ash and composite steel fiber evenly according to the proportion to obtain a premixed material;
[0092] S2, mixing the premixed material with other components and stirring to obtain a mixed base material;
[0093] S3, pouring the stirred mixed base material into the mold, and then vibrating the concrete to make the concrete dense;
[0094] S4. The formed concrete is cured to ensure its strength and durability. The curing method is to cover it with a wet cloth, with a relative humidity of 90% and a curing time of 15 days.
[0095] The properties of the final ultra-high performance concrete product are shown in Table 2.
[0096] Furthermore, the actual application parameter performance data of the ultra-high performance concrete prepared in the embodiment of the present invention are provided below, and the detailed test data are shown in Table 1-2.
[0097] Table 1: Parameter setting table for adding wood ash and special fiber to concrete.
[0098]
[0099]
[0100] Table 2: Comprehensive performance data of high performance concrete
[0101]
[0102] The following is an analysis of the performance gap between the ultra-high performance concrete prepared in 10 embodiments and one comparative example:
[0103] 1. Compressive strength
[0104] 15-hour compressive strength: The 15-hour compressive strength of the embodiment is between 32.7 MPa and 39.2 MPa, while the comparative example is only 24.9 MPa. The embodiment is significantly higher than the comparative example, indicating that by adjusting the amount of wood ash and special fiber, the early compressive strength of concrete can be significantly improved. With the change of the amount of wood ash and special fiber, the 15-hour compressive strength fluctuates to a certain extent, but is generally stable and much higher than the comparative example.
[0105] 30-day compressive strength: The 30-day compressive strength of the embodiment is between 207.2MPa and 228.2MPa, while that of the comparative example is 157.8MPa. The embodiment also far exceeds the comparative example, reflecting the advantage of the preparation method in long-term strength development. The strength difference between the embodiments is relatively small, indicating that the effect of adjusting the amount of raw materials within a certain range on the long-term compressive strength is relatively gentle.
[0106] 2. Slump
[0107] 0h slump: The 0h slump of the embodiment is between 162mm and 192mm, and that of the comparative example is 219mm. The initial slump of the comparative example is significantly higher than that of the embodiment, which may be due to the different composition or mix ratio of the raw materials in the comparative example, resulting in better fluidity. However, the slump of the embodiment can also meet certain construction requirements, and the slump has a certain change trend with the change in the amount of wood ash and special fiber.
[0108] 15h slump: The 15h slump of the embodiment is between 89 mm and 109 mm, and that of the comparative example is 142 mm. As time goes by, the slump of both the embodiment and the comparative example decreases, but the decrease in the slump of the embodiment is relatively small, indicating that the concrete prepared in the embodiment has certain advantages in maintaining fluidity.
[0109] 3. Flexural strength
[0110] The one-week flexural strength of the embodiment is between 25.71MPa and 28.61MPa, and that of the comparative example is 19.92MPa. The flexural strength of the embodiment is significantly higher than that of the comparative example, indicating that the addition of wood ash and special fibers has a significant effect on improving the flexural properties of concrete. There are also certain differences in the flexural strength between the embodiments, which may be related to the changes in the amount of raw materials used and the microstructure of the concrete.
[0111] In summary, by comparing the 10 embodiments with the comparative examples, it can be seen that the ultra-high performance concrete prepared by the preparation method has obvious advantages in terms of compressive strength, flexural strength, etc. Although the slump is slightly lower than that of the comparative example, it can still meet certain construction requirements. At the same time, by adjusting the amount of wood ash and special fiber, the performance of concrete can be regulated to a certain extent to meet the needs of different projects.
[0112] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a new ultra-high performance concrete material using special fibers, characterized in that: The method comprises the following steps: S1. Raw material preparation: prepare wood ash, special fiber, cement, mineral admixture, fine aggregate, coarse aggregate, water reducer and water; S2, raw material pretreatment: grinding the wood ash for refinement; S3, mixing and stirring: adding cement, mineral admixture, fine aggregate and coarse aggregate into a mixer, dry mixing for a certain period of time, adding treated wood ash and special fiber, continuing to stir evenly, and then adding water and water reducing agent and continuing to stir; S4. Forming and curing: pour the mixed concrete into a mold for forming. After curing, the formed concrete is cured to obtain a finished product of ultra-high performance concrete new material.
2. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: The raw materials are respectively as follows by weight: 50-85 parts of wood ash, 15-75 parts of special fiber, 420-480 parts of cement, 110-145 parts of mineral admixture, 120-150 parts of fine aggregate, 100-150 parts of coarse aggregate, 15-30 parts of water reducing agent and 170-280 parts of water.
3. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: The method for producing the special fiber comprises the following steps: Step 1: saw and split the original bamboo into pieces with a length of 10 to 40 mm, and then boil the original bamboo pieces in boiling water for 2 to 3 hours; Step 2: Take out the boiled bamboo pieces, crush them into bamboo strips, and then immerse the bamboo strips in a sodium hydroxide solution; Step 3, immersing the alkali-boiled bamboo fiber in a softener treatment solution for soaking treatment; Step 4: Soak the bamboo fiber obtained in step 3 in anhydrous ethanol, then wash it with tap water and dry it naturally.
4. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 3, characterized in that: In the step 2, the bath temperature is 100-110° C., the immersion time is 3-4 hours, and the bath ratio is 1:(25-30).
5. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 3, characterized in that: In the step 3, the bath temperature is 45-55° C., the treatment time is 2-3 hours, and the bath ratio is 1:(25-30).
6. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: In the step S4, the formed concrete is cured for 15 to 20 days at a temperature of 25° C. and a relative humidity of 90%.
7. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: The fine aggregate is quartz sand, river sand or machine-made sand, and the fineness modulus is between 2.4 and 2.
8.
8. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: The mineral admixture includes one or more of silica fume, fly ash and slag powder.
9. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: The cement is one of silicate cement, high belite cement and sulphoaluminate cement.
10. The method for preparing a new ultra-high performance concrete material using special fibers according to claim 1, characterized in that: The wood ash has a fineness of 700-800 meshes after grinding, and the length of the special fiber is controlled within a range of 2-2.5 cm and a diameter of 0.1-0.5 mm.
Citation Information
Patent Citations
Bamboo fiber concrete and preparation method thereof
CN103073244A
Bamboo fiber concrete and preparation method thereof
CN110357514A
Impermeable and anti-crack concrete and preparation method thereof
CN116730677A
Ultra-high performance concrete based on waste bamboo fiber toughening and internal curing and preparation method thereof
CN117720316A
Ultra-high performance fiber-reinforced concrete for improving construct ability, and manufacturing method for the same
KR1020160139208A
Cited By
Economical green low-carbon ultra-high performance concrete
CN119912222A
An economical green low-carbon ultra-high performance concrete
CN119912222B